PRODUKTIVITAS DAN BIAYA PEMANENAN KAYU MANGIUM (Acacia mangium) DI BKPH PARUNG PANJANG KPH BOGOR (Jurnal ForestrIndo, 2024)
The rising demand for wood has outpaced the production capabilities of Perhutani. This study analyzes the productivity and costs associated with forest harvesting. Productivity was measured by calculating the volume of wood and the work time for each stage of the harvesting process: felling (31 cycles), skidding (49 cycles), and transporting (11 cycles). We compared the costs incurred by workers with those incurred by Perhutani. Our findings reveal effective productivity rates of 26.32 m³/day for felling, 21.40 m³/day for skidding, and 19.8 m³/day for transporting. However, the actual productivity for these stages is only 5.54 m³/day. Harvesting in BKPH Parung Panjang operates under a contract system, where low productivity increases total worker costs. The costs incurred per cubic meter by fellers, skidders, and transporters are Rp32,030.55, Rp4,338.04, and Rp67,628.72, respectively. In comparison, the wages they receive are Rp35,000/m³, Rp16,666.67/m³, and Rp70,000/m³. The narrow margin between wages and expenses raises concerns about the welfare of these workers.